Visual Field Reconstruction in Hemianopia Using fMRI Based Mapping Techniques - Halbertsma, Hinke N.; Bridge, Holly; Carvalho, Joana; Cornelissen, Frans W.; Ajina, Sara (Frontiers in Human Neuroscience, 2021)
Purpose: A stroke that includes the primary visual cortex unilaterally leads to a loss of visual field (VF) representation in the hemifield contralateral to the damage. While behavioural procedures for measuring the VF, such as perimetry, may indicate that a patient cannot see in a particular area, detailed psychophysical testing often detects the ability to perform detection or discrimination of visual stimuli (‘blindsight’). The aim of this study was to determine whether functional Magnetic Resonance Imaging (fMRI) could be used to determine whether perimetrically blind regions of the VF were still represented in VF maps reconstructed on the basis of visually-evoked neural activity. Methods: Thirteen patients with hemianopia and nine control participants were scanned using 3T MRI while presented with visual stimulation. Two runs of a dynamic ‘wedge and ring’ mapping stimulus, totalling approximately 10mins, were performed while participants fixated centrally. Two different analysis approaches were taken: the conventional population receptive field (pRF) analysis and micro-probing (MP). The latter is a variant of the former that makes much fewer assumptions when modelling the visually evoked neural activity. Both methods were used to reconstruct the VF by projecting modelled activity back onto the VF. Following a normalization step, these ‘coverage maps’ can be compared to the VF sensitivity plots obtained using perimetry. Results: While both fMRI-based approaches revealed regions of neural activity within the perimetrically ‘blind’ sections of the VF, the MP approach uncovered more voxels in the lesioned hemisphere in which a modest degree of visual sensitivity was retained. Furthermore, MP-based analysis indicated that both early (V1/V2) and extrastriate visual areas contributed equally to the retained sensitivity in both patients and controls. Conclusions: In hemianopic patients, fMRI-based approaches for reconstructing the VF can pick up activity in perimetrically blind regions of the VF. Such regions of the VF may be particularly amenable for rehabilitation to regain visual function. Compared to conventional pRF modelling, MP reveals more voxels with retained visual sensitivity, suggesting it is a more sensitive approach for VF reconstruction.